Firekeeper's daughter - Boulley, Angeline (New York : Henry Holt and Company, 2021)
Daunis, who is part Ojibwe, defers attending the University of Michigan to care for her mother and reluctantly becomes involved in the investigation of a series of drug-related deaths.
Includes bibliographical references.
Keywords: Crime -- Juvenile fiction; Drugs -- Juvenile fiction; Undercover operations -- Juvenile fiction; Ojibwa Indians -- Juvenile fiction; Families -- Michigan -- Juvenile fiction; Racially mixed people -- Juvenile fiction; Detective and mystery fiction; Thrillers (Fiction); Young adult fiction